Antifungal Activity Of The Ethanolic Extract Of White Chrysanthemum Leaves (Chrysanthemum Morifolium (Ramat.) Hemsl. Against Candida Albicans And Pityrosporum Ovale - Melita Keliat, Jane; Azzahra, Nabilla; Lestari P, Dwi; Meliana Aritonang, Sonia (Journals of Ners Community, 2023)
White chrysanthemum (Chrysanthemum morifolium (Ramat.) Hemsl.) is an ornamental plant cultivated in Raya Village, Berastagi, North Sumatera which has potential as an antifungal. In this study, the antifungal activity test used agar diffusion method with paper disc as media in various concentrations, namely 500; 250; 50;10; 5; 2.5; 1.25; 0.625 mg/ml with positive control of ketoconazole and negative control of DMSO. Minimum Inhibitory Concentration (MIC) of ethanol extract of white chrysanthemum leaves against Candida albicans and Pityrosporum ovale at a concentration of 10 mg/ml with inhibition zone diameters of 6.83 mm and 7.76 mm